(untitled) (Scientific journal of the Fergana State University, 2024)
In this manuscript of research conducted in this article, the effectiveness of using the “Polymer composition” under salinity conditions, as well as physico-chemical and colloidal properties in field conditions, is presented (The saline soil of the Navoi region was used as a sample).